2004
DOI: 10.1007/s10038-003-0119-y
|View full text |Cite
|
Sign up to set email alerts
|

Six novel UDP-glucuronosyltransferase (UGT1A3) polymorphisms with varying activity

Abstract: Human UDP-glucuronosyltransferase (UGT) is a part of a major excretion pathway for endobiotics and xenobiotics. The UGT family of genes is highly polymorphic, and our aim is to describe novel polymorphisms at the UGT1A3 locus and determine how they alter substrate metabolism and drug reactions. One hundred healthy Japanese adults volunteered for the present study. We sequenced PCR-amplified fragments of the gene directly, and calculated the frequency of the genetic variations detected. To measure variant enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 42 publications
2
52
2
Order By: Relevance
“…Subjects 8 and 10 also had rapid excretion rates of N-hydroxyPhIP-N 2 -glucuronide, although these individuals were categorized as having a slow CYP1A2 phenotype. These two subjects, however, did have a UGT1A3*3 genotype, 4 which is associated with increased expression of UGT1A3 (40). The increased expression of UGT1A3 could have contributed to an increase in the formation of Nhydroxy-PhIP-N 2 -glucuronide (35).…”
Section: Discussionmentioning
confidence: 87%
“…Subjects 8 and 10 also had rapid excretion rates of N-hydroxyPhIP-N 2 -glucuronide, although these individuals were categorized as having a slow CYP1A2 phenotype. These two subjects, however, did have a UGT1A3*3 genotype, 4 which is associated with increased expression of UGT1A3 (40). The increased expression of UGT1A3 could have contributed to an increase in the formation of Nhydroxy-PhIP-N 2 -glucuronide (35).…”
Section: Discussionmentioning
confidence: 87%
“…Table 2 summarizes some functionally relevant UGT1A3 polymorphisms. The allele frequencies reported in two independent studies are similar, despite the different populations characterized in each study (Ehmer et al, 2004;Iwai et al, 2004). Iwai et al (2004) reported six single-nucleotide polymorphisms (SNPs) in exon 1 of UGT1A3.…”
Section: Ugt1a3mentioning
confidence: 82%
“…The allele frequencies reported in two independent studies are similar, despite the different populations characterized in each study (Ehmer et al, 2004;Iwai et al, 2004). Iwai et al (2004) reported six single-nucleotide polymorphisms (SNPs) in exon 1 of UGT1A3. Several mutants were expressed in COS-7 cells, and it was determined that contrary to several UGT mutants with diminished activity, the UGT1A3 variants W11R and W11R ĂŸ V47A exhibited much greater activity toward estrone than the wild type.…”
Section: Ugt1a3mentioning
confidence: 82%
“…These are similar to the previous data obtained from the Japanese. 22 Recently, linkages among the SNPs in 1A9, 1A7, 1A6, and 1A1 have been reported in Americans. 18 By our LD analysis, strong linkages were shown between the SNPs in 1A8 and 1A10, among those in 1A9, 1A7, and 1A6, and also between those in 1A3 and 1A1.…”
Section: Saeki Et Almentioning
confidence: 99%